South Africa : Who Goes to the Public Sector for Voluntary HIV/AIDS Counseling and Testing? - Thiede, Michael (World Bank, Washington, DC, 2013)
This is a study of how well public voluntary counseling and testing (VCT) programs for HIV/AIDS reach poor people in township areas of Cape Town, South Africa. The study covered three public clinics, where lay counselors from local nongovernmental organizations provided counseling. A clinic nurse was responsible for testing and notifying patients of the results. Waiting room interviews of 540 patients included questions about the patients' possessions and housing conditions designed to assess economic status. This information was compared with comparable information for people in South Africa as a whole, and in South Africa's urban areas, collected through a large-scale household Demographic and Health Survey. The principal finding was a much higher use of VCT services by lower- than higher-income patients. Almost 75 percent of VCT patients came from the poorest 40 percent of South Africa's urban population, fewer than 10 percent of patients belonging to the urban population's highest 40 percent. VCT patients were also poorer on average than patients attending the clinics for other reasons. The study also included focus group discussions with residents of the townships where the clinics were located, designed to determine what factors influence use of the clinics for VCT. These suggest that an important reason for the predominance of poor people among clinic patients was the poor reputation of the services provided by the clinics. This led better-off people to seek care from other, more expensive available sources.